Gas mixtures for quality control of the sTGC chambers. Issue 1 (January 2016) - Filippov, K A; Konovalov, S P; Mikenberg, G; Romaniouk, A; Shchukin, D; Shoa, M; Smakhtin, V; Smirnov, S Yu; Sosnovtsev, V V; Teterin, P E; Tikhomirov, V O; Tsekhosh, V I; et al.
Abstract: sTGC chambers are designed to operate at super-LHC conditions and will be installed in place during Phase-I upgrade of the ATLAS muon spectrometer. These chambers will provide precise coordinate measurements of the charged particle tracks and level 1 trigger for high pT muons. It is critical for the ATLAS detector to ensure a robust operation of these chambers during entire sLHC period. A quality control procedure based on X-ray scanner is being developed. Choice of the active gas for these tests is a very important issue. On one hand it should allow to find different types of chamber production defects, on the other hand one has to be sure that found problems are essential for the detector operation in future. Studies of the operation of the sTGC chamber prototype under X-ray irradiation with two gas mixtures (n- pentane/CO2 and CO2 ) were performed. The prototype was irradiated by X-rays with energy up to 50 keV. Particular attention was paid to the study of the "hot" chamber regions.